A nearly missed Hashimoto’s Thyroiditis: A case of refractory anaemia / Sharifah Azimah Wan Ali ... [et al.] - Wan Ali, Sharifah Azimah; Mohamed-Yassin, Mohamed-Syarif; Abdul-Razak, Suraya (Universiti Teknologi MARA Cawangan Selangor, 2020)
This is a case of a 68-year-old man who was diagnosed late with Hashimoto’s thyroiditis following a few admissions for symptomatic anaemia. Although hypothyroidism is common among the elderly, the classic symptoms are less likely to be evident and anaemia can be the first sign of hypothyroidism. This patient had multiple comorbidities including ischaemic heart disease, diabetes and chronic kidney disease which might have contributed to the delay in finding the underlying cause of his anaemia. He initially presented with symptomatic anaemia and received blood transfusions and iron supplementation. On subsequent follow up, his anaemia failed to improve. He was then referred to our primary care clinic. Hashimoto’s thyroiditis was diagnosed based on his clinical features, thyroid function test results and anti- thyroid peroxidase level. This case highlights the importance of determining the cause of anaemia as his haemoglobin level improved significantly after thyroxine was commenced. It also serves as a reminder that hypothyroidism should be considered in patients with anaemia, especially in those with uncertain aetiology.